Developing Electronic Student Worksheet based on Probing Prompting Learning Method using Google Form on Social Arithmetic - Levia, Tilza; Maulidiya, Della; Siagian, Teddy Alfra (Universitas Islam Negeri Sunan Kudus, 2023)
This study aims to feasibility electronic student worksheet with the Probing Prompting learning method using Google Form on social arithmetic material for valid, practical, and effective. This research was used an ADDIE model, that consist of analyze, design, development, implementation, and evaluation. The research instrument include of validation sheets, practicality sheets, and tests of mathematical problem solving abilities. This research produced an electronic student worksheets based on probing prompting usng Google Form on social arithmetic material. of seventh-grade students was included in the following criteria: 1) Very valid based on content assessment, construct assessment, language assessment, media assessment; 2) Practical based on 11 aspects of assessment; 3) Effectiveness based on classical learning mastery, namely 90% of students who complete score ≥70 and the results of the N-Gain calculation of problem solving abilities with an average N-Gain of 0.77 are in the high category. Penelitian ini bertujuan untuk menghasilkan lembar kerja peserta didik berbentuk elektronik dengan metode pembelajaran Probing Prompting menggunakan Google Form materi aritmatika sosial yang valid, praktis, dan efektif. Penelitian ini adalah penelitian dan pengembangan model ADDIE, yaitu analisis, desain, pengembangan, implementasi, dan evaluasi. Instrumen penelitian ini terdiri dari lembar validasi, lembar kepraktisan, dan tes kemampuan pemecahan masalah matematis. Penelitian ini menghasilkan LKPD elektronik berbasis probing prompting menggunakan Google Form pada materi aritmatika sosial peserta didik kelas VII memenuhi kriteria: 1) Sangat valid berdasarkan aspek penilaian isi, aspek konstruk, aspek bahasa, aspek media; 2) Praktis; 3) Efektif berdasarkan ketuntasan belajar klasikal yaitu 90% peserta didik yang tuntas memperoleh nilai ≥70 dan hasil perhitungan N-Gain kemampuan pemecahan masalah dengan rata-rata N-Gain 0,77 berada pada kategoti tinggi.